Growth performance of Jatropha curcas L. seedlings and some properties of acidic, low fertility grassland soil amended with biowaste compost - Cuevas, Virginia C. (2009)
A pot experiment was conducted to observe the effects of various levels of biowaste compost on selected properties of red, low fertility, acidic grassland soil collected from Tanay, Rizal and on the growth performance of Jatropha curcas L. seedlings. Market biowaste compost added at 16-46% (∼5:1-1:1 soil-to-compost ratio) w/w significantly improved the following properties with mean values: 1) soil pH (4.2-6.8), 2) water-holding capacity (91-111%) and cation exchange capacity (15-41) (cmol +/kg), respectively, from control (pure grassland soil) to treated (compost-amended) soil. Bacterial and fungal populations significantly increased only when compost was added at 30% (∼2:1 soil-compost) to 46% (∼1:1soil-compost). J. curcas L. seedlings grown in composttreated potting media had significantly higher dry shoot and root dry weights compared with those grown in pure soil only. Growth improvement was proportional to the amount of compost added to the soil. Improvement of soil physical and chemical properties was optimum at 16% added compost. Any further increase in compost application did not result in further improvement of the tested soil properties. The use of biowaste to improve productivity of grassland areas which cover about 30% of the country's total land area is highly recommended.
Keywords: Compost